The Impact of Social Media Engagement on Brand Loyalty: A Strategic Approach for Marketing Management in the Digital Age - Dr. Podilapu Hanumantha Rao, Dr. Sanjay J. Bhayani; Rama Devi Seshapu (Journal of Informatics Education and Research, 2025)
In this study, the attention is largely on the consequence of social media in the current marketing systems with emphasis on the aspects of consumer behavior and brand loyalty in the Delhi-NCR region. The primary aim is to understand how social media as the marketing platform, with different possible platforms, impacts the consumer interaction and purchasing decisions. An approach that relied on surveys was employed where 175 respondents were contacted by using a clearly structured questionnaire. This tool included questions that had 5-point Likert scale and multiple choices questions to determine the level of consumer involvement, contentment, and allegiance. A diverse range of statistical models were used in the study to analyze data collected such as descriptive analysis, chi-square tests, ANOVA, correlation tests, and regression analysis. The results show that there is a high connection between stronger brand loyalty and satisfaction with consumers having high levels of interaction through social media. Further, the aspects of demographics such as age and educational level were also found to have influence on the classes of consumers on social media marketing. These findings show that businesses should enhance their involvement strategies, closely using influencers and user-generated content, to foster better connections with their consumers and foster loyalty. The conclusion of the work is made by noting how relevant social media has become in driving brand success and offering recommendations to marketers to ensure they effectively leverage the said channels in their marketing efforts.